EFIKASI DIRI GURU DAN LITERASI DIGITAL SERTA KONTRIBUSINYA TERHADAP EFEKTIVITAS PROSES PEMBELAJARAN DALAM JARINGAN - Ipong Dekawati; Wahyu Trisno (STKIP Subang, 2023)
The effectiveness of the learning process in the network is one that needs attention, especially after the 2019 pandemic where the use of the network in the learning process is a must. With the effectiveness of the learning process in a good network, students can get maximum education in the learning process. Based on the results of initial observations made by researchers, it was found that the effectiveness of the learning process in the network was not optimal. This is thought to be caused by low teacher self-efficacy and teacher digital literacy. Therefore, it is necessary to do research to test the truth. This study uses a survey method with a quantitative approach, as well as correlational and regression techniques. Data collection technique through a Likert scale questionnaire to 53 respondents who are elementary school teachers. The results of the data analysis show that (1) Teacher self-efficacy contributes to the effectiveness of the learning process in the network, (2) Digital literacy contributes to the effectiveness of the learning process in the network, (3) Teacher self-efficacy and digital literacy jointly contribute to the effectiveness of the learning process . Principals can provide special training related to the use of digital products or media, especially regarding the use of software. Additional knowledge about software is no longer an added value but has become a necessity in today's information technology era. The school principal is deemed necessary to provide training with the aim of making teachers accustomed to choosing digital literacy. With the circulation of various sources of information, ideally teachers can find sources of information that have high credibility.